GDF15 acts synergistically with liraglutide but is not necessary for the weight loss induced by bariatric surgery in mice - Henriette Frikke-Schmidt; Karin Hultman; Joseph W. Galaske; Sebastian B. Jørgensen; Martin G. Myers, Jr.; Randy J. Seeley (Molecular Metabolism, 2019)
Objective: Analogues of GDF15 (Growth Differentiation Factor 15) are promising new anti-obesity therapies as pharmacological treatment with GDF15 results in dramatic reductions of food intake and body weight. GDF15 exerts its central anorexic effects by binding to the GFRAL receptor exclusively expressed in the Area Postrema (AP) and the Nucleus of the Solitary Tract (NTS) of the hindbrain. We sought to determine if GDF15 is an indispensable factor for other interventions that cause weight loss and which are also known to act via these hindbrain regions. Methods: To explore the role of GDF15 on food choice we performed macronutrient intake studies in mice treated pharmacologically with GDF15 and in mice having either GDF15 or GFRAL deleted. Next we performed vertical sleeve gastrectomy (VSG) surgeries in a cohort of diet-induced obese Gdf15-null and control mice. To explore the anatomical co-localization of neurons in the hindbrain responding to GLP-1 and/or GDF15 we used GLP-1R reporter mice treated with GDF15, as well as naïve mouse brain and human brain stained by ISH and IHC, respectively, for GLP-1R and GFRAL. Lastly we performed a series of food intake experiments where we treated mice with targeted genetic disruption of either Gdf15 or Gfral with liraglutide; Glp1r-null mice with GDF15; or combined liraglutide and GDF15 treatment in wild-type mice. Results: We found that GDF15 treatment significantly lowered the preference for fat intake in mice, whereas no changes in fat intake were observed after genetic deletion of Gdf15 or Gfral. In addition, deletion of Gdf15 did not alter the food intake or bodyweight after sleeve gastrectomy. Lack of GDF15 or GFRAL signaling did not alter the ability of the GLP-1R agonist liraglutide to reduce food intake. Similarly lack of GLP-1R signaling did not reduce GDF15's anorexic effect. Interestingly, there was a significant synergistic effect on weight loss when treating wild-type mice with both GDF15 and liraglutide. Conclusion: These data suggest that while GDF15 does not play a role in the potent effects of VSG in mice there seems to be a potential therapeutic benefit of activating GFRAL and GLP-1R systems simultaneously. Keywords: GDF15, GLP-1, Bariatric surgery, Liraglutide